Targeted Nanoparticles for Pediatric Leukemia Therapy - Basha, Riyaz; Sabnis, Nirupama; Heym, Kenneth; Bowman, W. Paul; Lacko, Andras G. (Frontiers in Oncology, 2014)
The two major forms of leukemia, acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) account for about one third of the malignancies diagnosed in children. Despite the marked successes in ALL and AML treatment, concerns remain regarding the occurrence of resistant disease in subsets of patients the residual effects of therapy that often persist for decades beyond the cessation of treatment. Therefore, new approaches are needed to reduce or to avoid off target toxicities, associated with chemotherapy and their long term residual effects. Recently, nanotechnology has been employed to enhance cancer therapy, via improving the bioavailability and therapeutic efficacy of anti-cancer agents. While in the last several years, numerous review articles appeared detailing the size, composition, assembly and performance evaluation of different types of drug carrying nanoparticles, the description and evaluation of lipoprotein based drug carriers have been conspicuously absent from most of these major reviews. The current review focuses on such information regarding nanoparticles with an emphasis on high density lipoprotein (HDL)-based drug delivery systems to examine their potential role(s) in the enhanced treatment of children with leukemia.